Redesign of the "Si Bangga" Application at the Purbalingga Narcotics Agency Using the Design Sprint Method - Nuraziz, Reza Eka; Hamdi, Aulia (Journal of Multimedia Trend and Technology, 2024)
In the contemporary era driven by technological developments, global transformations encompass every aspect of human life, where the digital revolution, the internet, social media, and artificial intelligence are the foundations of change in communication, industry, and human interaction with the environment. While these developments bring significant benefits, they also pose challenges for privacy, security, and access gaps. In this context, the National Narcotics Agency (BNN) of Purbalingga Regency responded by launching the SiBangga application to improve efficiency in providing information and services related to the main tasks of the BNN through a mobile platform. Although this application is a progressive step, competitor analysis shows significant potential for development in terms of user engagement, responsiveness, and functionality. This study aims to identify areas that need to be updated in SiBangga to more effectively meet user needs and overcome competitor weaknesses. Using the Design Sprint method as the basis for the redesign, this study will produce an updated user interface to provide a better experience, ensure active engagement, and meet quality standards in the competitive digital technology market. Thus, this study not only responds to market and technology dynamics but also makes a positive contribution to the development of the SiBangga application for a more innovative and competitive future.